Effectiveness of Hold-Relax Proprioceptive Neuromuscular Facilitation in Enhancing Knee Flexion after Total Knee Replacement: A Randomized Controlled Trial - Hussain, Mir Arif; Qureshi, Muhammad Faisal; Tabassum, Shamma; Imran, Ayesha; Arshad, Sundas; Ali, Sonia (Indus Journal of Bioscience Research, 2025)
Background: For end-stage osteoarthritis, total knee replacement (TKR) is a standard surgical procedure; nevertheless, postoperative knee flexion is frequently restricted, which delays functional rehabilitation. Although physiotherapy is essential to recovery, there is disagreement over the best stretching technique for restoring range of motion (ROM). Although its use in post-TKR therapy is not well established, proprioceptive neuromuscular facilitation (PNF), in particular the hold-relax approach, has demonstrated promise in enhancing flexibility across musculoskeletal disorders. Objective: The purpose of this study was to compare the PNF hold-relax technique to normal therapy after TKR in order to assess how well its improved knee flexion range of motion. Methods: Thirty-five patients (aged 45–65) who had unilateral or bilateral TKR at a tertiary care institution participated in a single-blind randomized controlled experiment. Participants were randomly assigned to one of two groups: the experimental group received the same program with PNF hold-relax stretching, while the control group received routine postoperative therapy. A goniometer was used to quantify knee flexion range of motion both before and after the four to five-month intervention. Paired-sample t-tests were used to examine the data, and p < 0.05 was considered significant. Results: The participants' average age was 57.1 years, and 74.3% of them were female. The range of baseline ROM was 45° to 70°. In contrast to the control group, which saw less increases, 91.4% of patients in the PNF group attained flexion ≥120° after the intervention. Statistically significant improvements were seen (p < 0.05). Conclusion: PNF hold-relax, a safe and affordable supplement to traditional physiotherapy, dramatically improves postoperative knee flexion in TKR patients when incorporated with regular rehabilitation.